THE INFLUENCE OF SPEED LIMITS ON THE ENERGY PERFORMANCE OF TRAINS - Kurgan, M. B.; Markova, O. S. (Science and Transport Progress, 2007)
The technique and results of researches of efficiency of elimination of speed limitations of train movements are explained